2011 Fourth International Symposium on Parallel Architectures, Algorithms and Programming 2011
DOI: 10.1109/paap.2011.12
|View full text |Cite
|
Sign up to set email alerts
|

Option Pricing on the GPU with Backward Stochastic Differential Equation

Abstract: Abstract-In this paper, we develop acceleration strategies for option pricing with non-linear Backward Stochastic Differential Equation (BSDE), which appears as a robust and valuable tool in financial markets. An efficient binomial lattice based method is adopted to solve the BSDE numerically. In order to reduce the global memory access frequency, the kernel invocation is avoided to be performed on each time step. Furthermore, for evaluating the affect of load balance to the performance, we provide two differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…For FBSDEs, Tran (2010) reconstructed the four step scheme with some new conditions, and combined it with the Schwarz waveform relaxation method to parallelize the system of quasilinear parabolic equations. Peng et al (2011) designed and implemented acceleration strategies on parallel GPUs for option pricing with BSDEs. Liu et al (2011) used X10's properties to implement option pricing with BSDEs.…”
Section: Other Methodsmentioning
confidence: 99%
“…For FBSDEs, Tran (2010) reconstructed the four step scheme with some new conditions, and combined it with the Schwarz waveform relaxation method to parallelize the system of quasilinear parabolic equations. Peng et al (2011) designed and implemented acceleration strategies on parallel GPUs for option pricing with BSDEs. Liu et al (2011) used X10's properties to implement option pricing with BSDEs.…”
Section: Other Methodsmentioning
confidence: 99%
“…Some acceleration strategies based on Graphics Processing Unit (GPU) computing have been developed for the pricing problems in finance, however, a very little of them are BSDE-based approach. These works can be found in [7,11,22], where the acceleration strategies are applied on numerical methods of convergence order not higher than 2.…”
Section: Introductionmentioning
confidence: 99%
“…The parallel program with CUDA achieved high speedups and showed that the GPU architecture is well suited for solving the BSDEs in parallel. Peng et al [Peng et al, 2011] developed acceleration strategies for option pricing with non-linear BSDEs using a binomial lattice based method. To increase the speedup, they reduce the global memory access frequency by avoiding the kernel invocation on each time step.…”
Section: Introductionmentioning
confidence: 99%